Gender Equity Insights 2019: Breaking through the Glass Ceiling - Cassells, Rebecca; Duncan, Alan (Bankwest Curtin Economics Centre, 2019)
Glass ceilings have featured heavily in Australia’s workplaces for centuries but in recent years significant changes have been made.